PERANAN RUANG PUBLIK PERKOTAAN TERHADAP PENGEMBANGAN MODAL SOSIAL DAN PEREDAM PATOLOGI SOSIAL : survey pada siswa sma di Kota Bandung - Daluarti, Meitri Hening Chrisna (2015)
The rise of juvenile delinquency and other social pathology currently has raised concerned various parties, and all of it into a weak indicator of social capital. Social capital is formed through the social structure, family, education, and the built environment (Aldridge, Halpern, and Fitzpatrick, 2002, p. 15). Part of the built environment is a public space, which should be accessible to the public either individually or in groups (Carr et al, 1992, pp. 50-51). NCSS aims that one theme of learning social studies are humans and the environment which has the meaning of human life and can not be separated from the environment or space, including social skills as a dimension of social capital (Maryani, 2011, pp. 12-13). This study aims to examine the role of public spaces to social capital and social phatology absorbers among high school students in Bandung, using a quantitative approach and survey method. Total sample of 1140 students spread across 38 public and private high school. The data is processed by using path analysis. The findings of this study are as follows. (1) There is a relationship between the physical and non-physical components of public space; (2) There is an influence of the physical components of a public space for the development of social capital; (3) There is an influence of the physical components of the public space of the damper social pathology; (4) There is an influence of non-physical components of a public space for the development of social capital; (5) there is a positive effect of non-physical components of public space for social pathology; (6) There is a positive effect of social capital on social pathology; (7) The components of physical and non-physical component of public space simultaneously affect the social capital; and (8) physical component and non-physical component of public space simultaneously affect the social pathology. Recommendations from this study: (1) for the city government, the existence of public spaces need to be supplemented in accordance with the needs of citizens, in addition to the need to consider aspects of function and social aspects; considering public space has become a means of self students in a positive way; (2) for social studies teachers, public space with all the phenomenon may be a place and a source of interesting and contextual learning, so that learning will not bored; (3) for further research is recommended to assess the perception according to adolescent psychological condition that can develop a form of public space are more instrumental to the development of social capital and social pathology reducer. Maraknya kenakalan remaja dan patologi sosial lain saat ini telah menimbulkan keprihatinan berbagai pihak, dan semua itu menjadi indikator lemahnya modal sosial. Modal sosial dibentuk melalui struktur sosial, keluarga, pendidikan, dan lingkungan binaan (Aldridge, Halpern, dan Fitzpatrick, 2002, hlm. 15). Bagian dari lingkungan binaan adalah ruang publik, yang seharusnya dapat diakses oleh masyarakat baik secara individu maupun kelompok (Carr dkk, 1992, hlm. 50-51). Salah satu tema pembelajaran IPS menurut NCSS adalah manusia dan lingkungan yang mempunyai makna kehidupan manusia dan tidak dapat dipisahkan dari lingkungan atau ruang, termasuk di dalamnya keterampilan sosial sebagai dimensi dari modal sosial (Maryani, 2011, hlm. 12-13). Penelitian ini bertujuan mengkaji peran ruang publik terhadap modal sosial dan peredam patologi sosial di kalangan siswa SMA Kota Bandung, dengan menggunakan pendekatan kuantitatif dan metode survey. Jumlah siswa sampel sebanyak 1140 yang menyebar di 38 SMA Negeri dan Swasta. Data diolah dengan mempergunakan analisis jalur. Temuan penelitian ini adalah sebagai berikut. (1) Terdapat hubungan antara komponen fisik dan non fisik ruang publik; (2) Terdapat pengaruh antara komponen fisik ruang publik terhadap pengembangan modal sosial; (3) Terdapat pengaruh antara komponen fisik ruang publik terhadap peredam patologi sosial; (4) Terdapat pengaruh antara komponen non fisik ruang publik terhadap pengembangan modal sosial; (5) terdapat pengaruh positif antara komponen non fisik ruang publik terhadap patologi sosial; (6) Terdapat pengaruh positif antara modal sosial terhadap patologi sosial; (7) Komponen fisik dan komponen non fisik ruang publik secara simultan berpengaruh terhadap modal sosial; serta (8) Komponen fisik dan komponen non fisik ruang publik secara simultan berpengaruh terhadap patologi sosial. Rekomendasi dari penelitian ini: (1) untuk pemerintah kota, keberadaan ruang publik perlu ditambah sesuai dengan kebutuhan warga, selain itu perlu di pertimbangkan aspek fungsi dan aspek sosialnya;mengingat ruang publik telah menjadi sarana mengaktualisasikan diri siswa secara positif; (2) untuk para guru IPS, ruang publik dengan segala fenomenanya dapat menjadi tempat dan sumber belajar yang menarik dan kontekstual, sehingga pembelajaran tidak membosankan; (3) untuk penelitian selanjutnya direkomendasikan untuk mengkaji persepsi sesuai dengan kondisi psikologi remaja sehingga dapat mengembangkan bentuk ruang publik yang lebih berperan untuk pengembangan modal sosial dan peredam patologi sosial.